Exercícios terapêuticos supervisionados por telemonitoramento em grupo com mulheres em pós-operatório de câncer de mama: um ensaio clínico randomizado - Pereira, Jennifer Rego (2024)
INTRODUCTION: Breast cancer is the most common neoplasm in women. The treatment consists of a multimodal approach, which, although it allows a good survival rate, can negatively impact functionality and quality of life. Given the need for long-term monitoring of this population and the difficulties observed in outpatient follow-up, telemonitoring could be an option for offering rehabilitation programs. The Pilates Method has been a useful resource as a physiotherapeutic intervention in rehabilitation processes, including for cancer patients. In this context, the synchronous and group format of telemonitoring in the recovery and/or maintenance of functionality for patients with breast cancer, and its feasibility, still need to be evaluated. OBJECTIVE: To evaluate the effectiveness of a supervised exercise program, based on the Pilates Method, through group telemonitoring in women undergoing surgery for breast cancer. METHODOLOGY: This is a randomized non-inferiority clinical trial with women aged 25 to 65 years, within 24 months of post-operative breast cancer, with stages I to III and who have completed adjuvant therapy, except hormone therapy. . The participants underwent an assessment of physical capacity and functionality (WHODAS 2.0), in addition to the collection of sociodemographic and clinical data. Participants were randomized into two intervention groups (1:1): telemonitoring group: exercises based on the Solo Pilates Method by synchronous telemonitoring and in-person group with face-to-face exercises, both twice a week, for 60 minutes, for 8 weeks. The primary outcomes were: physical capacity, functionality; secondary outcomes: adverse effects, adherence and participant satisfaction. Statistical analysis was performed using the Chi-square test for categorical variables and Student's t test and mean difference for continuous variables. A 95% confidence interval and p-value < 0.05 were considered. RESULTS: Initially, 44 women were selected according to the eligibility criteria. Of these, 10 were excluded after applying the criteria, 11 did not attend for assessment (baseline) and 1 was excluded due to cognitive difficulty (recruitment rate of 50%). Thus, 22 women were evaluated and randomized, 10 in the telemonitoring group and 12 in the in-person group. Partial data from 22 women are presented. The average age was 50.7 (8.8) years. There was no difference between the groups in sociodemographic, clinical and oncological treatment characteristics before the intervention. The ECR retention rate was 72.7% (n=16) and the adherence rate to the protocol was 76% in the telemonitoring group and 80% in the in-person group. Of the 11 participants who completed follow-up so far and were reevaluated, 6 were telemonitoring and 5 were in person. Regarding functionality (WHODAS), we observed that there was no difference between the groups both before and after the intervention, however, there was a decrease in disability after the intervention for the total sample. Similar result for physical capacity. No serious adverse effects were observed during the interventions, with the most reported symptoms being: dizziness, nausea and pain in the upper shoulder homolateral to the surgery. Participants showed a high degree of satisfaction in both groups. CONCLUSION: Preliminary data indicates challenges in recruiting participants regarding eligibility. Women seem to have good adherence to telemonitoring and in-person interventions. The exercise protocol based on the Pilates Solo method through telemonitoring appears to be non-inferior to the in-person format in terms of functionality and physical capacity in women who have undergone treatment for breast cancer. However, these data should be interpreted with caution until the study is completed.